Analisis Pengujian Sistem Pengiriman Barang Menggunakan Black Box Testing - Kusuma, Abdi Pandu; Rahmat, Muhammad Faried; Rofiq, Arta Ainur (LPPM STIKI MALANG, 2023)
Poultry Shop Blitar is stores that provides animal feed for the Blitar city area. The main activity of this business is the distribution of animal feed to the surrounding areas of Blitar city. Problems began to arise as the demand for animal feed delivery increased. This prompted the store to optimize delivery by finding the nearest route. In this study, the black box method was used to test the optimization of the application system for goods delivery. The research aimed to test the display of the goods delivery system application using black box testing and then determine the accuracy of the testing of the built application. Data collection methods included interviews, observations, literature studies, and documentation to effectively gather data. The subjects of this study were the employees involved in the goods delivery at Poultry Shop. The testing results for several application displays yielded a final testing accuracy percentage of 62.5%, with an average testing result of 75% for the main goods delivery form and 50% for the goods delivery form dated May 20th.